2005
DOI: 10.1111/j.1440-1819.2005.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent cognitive dysfunction in patients with obsessive‐compulsive disorder: A naturalistic study

Abstract: The purpose of the present study was to investigate the changes in the cognitive dysfunctions of patients with obsessive-compulsive disorder (OCD) over a 1-year period of pharmacological treatment. Twenty-one OCD patients and 20 normal subjects underwent neuropsychological tests and clinical evaluations on three separate occasions (baseline, 4 months, and 1 year after the start of medications). OCD patients continued to show significant impairments in the following cognitive measures compared with the normal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 39 publications
7
46
0
Order By: Relevance
“…However, percentage of medication was equal in washers and checkers and the meta-regression analysis did not find a significant effect of medication on participants' performance. This finding corresponds well with previous studies demonstrating that medication status had little or no significant effect on neuropsychological test performance (Mataix-Cols, Alonso, Pifarré, Menchón, & Vallejo, 2002;Roh et al, 2005;Simpson et al, 2006). Besides, since all included studies were cross-sectional it remains unclear whether the observed cognitive deficits in checkers compared to washers represent state or trait deficits.…”
Section: Limitationssupporting
confidence: 86%
“…However, percentage of medication was equal in washers and checkers and the meta-regression analysis did not find a significant effect of medication on participants' performance. This finding corresponds well with previous studies demonstrating that medication status had little or no significant effect on neuropsychological test performance (Mataix-Cols, Alonso, Pifarré, Menchón, & Vallejo, 2002;Roh et al, 2005;Simpson et al, 2006). Besides, since all included studies were cross-sectional it remains unclear whether the observed cognitive deficits in checkers compared to washers represent state or trait deficits.…”
Section: Limitationssupporting
confidence: 86%
“…Notwithstanding, we must underline that all the patients included in the current study had been diagnosed with tic disorder as the primary problem. Recent investigations using the ROCF with adult OCD patients found comparable group discrepancies to ours in immediate and delayed recall, with relatively normal performances on the copy score (Kim, Park, Shin, & Kwon, 2002;Kim et al, 2003;Roh et al, 2005). However, the specificity of this nonverbal memory deficit has not previously been clearly established when comparing OCD with other psychiatric population (Moritz et al, 2005).…”
Section: Discussionmentioning
confidence: 54%
“…In addition, there is a growing body of literature to support the acute cognitive benefits, in particular executive functioning, of aerobic exercise (Colcombe & Kramer, 2003). Deficits in executive functioning have been consistently demonstrated among patients with OCD (Penades, Catalan, Andres, Salamero, & Gasto, 2005;Roh et al, 2005). Therefore, given that executive dysfunction is the primary area of concern in OCD and exercise may improve functioning in this domain, it is possible that acute improvements in obsessions and compulsions may be mediated by improvements in executive control.…”
Section: Discussionmentioning
confidence: 94%